Proponemos acciones personales y colectivas para el uso sostenible del agua - Nureña Díaz, Franchesca Alejandra (2022)
This professional sufficiency work aims to determine viable proposals that we can make personally and collectively for the sustainable use of water, in students of the 3rd year of secondary section "I" of the I.E. "San Juan" 2022. For the development of the learning design we had a population and sample of 24 students. A thorough investigation was also carried out, which is the basis of the class design, which corresponds to the scientific support, considering the theoretical development of the topic, such as the definition of water, the sustainable use of water, water pollution and problems of water management and use in La Libertad. In the pedagogical support, the moments of a didactic session have been detailed, such as the beginning, development and closing, the procedures that were carried out were methodological, making use of a series of resources such as images, techniques such as observation, group work, brainstorming, dialogue; as well as didactic principles, such as the principle of socialisation, creativity and autonomy. In conclusion, the development of the learning design with the students resulted in the realisation of personal and collective proposals for the sustainable use of water.